Tripropyl Chitosan iodide-based gel polymer electrolyte as quasi solid-state dye sensitized solar cells - Yahya, W.Z.N. (Trans Tech Publications Ltd, 2020)
Electrolyte as one of the major components in dye sensitized solar cells (DSSCs) plays an important role in dye regeneration and as the inner charge carrier transport between electrodes. Gel polymer electrolyte is a potential alternative to liquid electrolytes which suffer of leakage and solvent evaporation. In this present research, functionalization of chitosan by the quaternization reaction of chitosan with iodopropane forming tripropyl chitosan iodide is proposed for the preparation of gel polymer electrolyte. Tripropyl chitosan iodide was characterized by nuclear magnetic resonance spectroscopy (NMR), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Four different polymer electrolytes were tested at different compositions in presence of iodide/triiodide redox salt and imidazolium ionic liquid in DSSCs configurations. The results show that the gel polymer electrolyte containing the tripropyl chitosan iodide in presence of 1-propyl-3-methylimidazolium iodide ionic liquid showed better performance with power conversion efficiency of 0.415 as compared to the gel polymer electrolyte film without ionic liquid with power conversion efficiency of 0.075. The results shown the synergistic effects of the polycationic tripropyl chitosan iodide with the ionic liquid 1-propyl-3-methylimidazolium iodide on the photovoltaic performance. Â© 2020 Trans Tech Publications Ltd, Switzerland.